Phased array building blocks for 5G networks - Scalise, Giuseppe; Crupi, Felice; Boccia, Luigi (Università della Calabria, 2021)
5G will have to support a multitude of new applications with a wide variety of requirements, including higher user data rates and network capacity, reduced latency, improved energy efficiency, and so on. These aspects will lead to a radical change in network architecture from different points of view. For example, the densification of small cells in the access network will produce massive traffic to the core network and an increment of the interference due to the lower inter-cell distance. In particular, millimeter waves (mm-waves) bands, due to their large unlicensed and lightly licensed bandwidths, have become a promising candidate for the next-generation wireless communications, to accommodate users demand for multi-Gbps data rates, but this will move the attention to the complexity and the criticality of the base station antenna systems. In fact, because of the carrier frequency increment, it will be necessary to use large-scale antennas to compensate channel losses which are significant in the millimeter wave bands. Furthermore, the combined use of phased arrays and massive MIMO technologies will be required to achieve a better usage of the radio channel, by implementing more accurate spatial selectivity techniques, thus resulting in an increased network capacity and signal-to-noise (SNR) performance. Among the spectrum portions used in the access segment, the Ka-band is the most interesting and attractive to implement low-cost wideband antenna systems with high steering capability along both azimuth and elevation directions and good performance in terms of directivity. On the other side, the shift to higher frequencies required by these systems will imply a decrease in the space available for the integration of the chip containing the transceiver and all the necessary RF circuitry. Therefore, hardware integration will be a key element to be taken into consideration for the development of the fifth-generation phased array systems. The main object of this work is to analyze and design different building blocks of phased array systems operating in Ka-band for 5G applications. The research activities presented in this dissertation can be summarized into two parts. In the first part, a 32-element dual-polarized array operating in n257 band (26.5-29.5 GHz) for 5G phased array systems is presented, where a novel ultra-low profile dual-polarized Magneto-Electric dipole has been employed as the radiating element. This array system has been thought to be used in a 5G small cell, where the radiated beam should be directed along azimuth and elevation considering the scan range (±55°𝐴𝑍,±20°𝐸𝐿) to increase both spatial selectivity and network capacity. In the second part, the attention has been focused on the study and the design of variable gain amplifiers (VGAs) in a standard 0.13 μm SiGe BiCMOS technology for 5G phased array applications. At first, the performance of a Ka-band conventional single-stage NMOS voltage variable attenuator (VVA) has been compared with a novel Ka-band hybrid single-stage VVA with improved power handling capability and linearity, where two shunt HBT transistors act as varistors to change continuously the attenuation state of the cell. At this point, a monolithically-integrated dual-stage VGA with higher power capability and wider gain tuning range based on the use of VVA circuit as control element has been developed. This component should be employed directly as an end-stage variable gain PA in Si-based 5G transmitters or as a driver in hybrid Si/GaN-based or Si/GaAs-based 5G transceivers.
Dottorato di Ricerca in Information and Communication Technologies (ICT), Ciclo XXXIII
Keywords: 5G; Millimeter Wave; Beamforming systems; Antenna arrays